Penerapan Algoritma Decision Tree C4.5 dalam Pemilihan Leader Warrior pada Game Android Power Ranger Legacy Wars - Rochmat Setiyawan (STMIK Budi Darma, 2019)
The variety of virtual game champions Power Ranger Legacy Wars on the smartphone platform makes users confused in determining the formation of the team. But the choice of team formation during the process of playing video games requires a thorough skill and study that can sometimes lead to unexpected problems due to poor choices and can affect the game. In this paper, we will present the decision tree C4.5 algorithm process method to solve the problem of team selection in the game, then we will discuss the results to see whether the method chosen provides the right decision that will help players choose the warrior ranger easily in the game